Environmental Sanitation Analysis of Dengue Fever Disease - Intan Manirah Niksan; Akhmad Dwi Priyatno; Lilis Suryani; Yusnilasari (School of Health Sciences Al-Ma'arif, 2025)
Dengue Hemorrhagic Fever (DHF) is caused by the dengue virus transmitted by the Aedes aegypti mosquito or Aedes albopictus. The characteristics of the infectious vector determine the spread and timing of the occurrence of infection. The habitat of aedes mosquitoes is generally in regions with tropical climates, high rainfall, and hot and humid temperatures. The design of this study is quantitative with a cross sectional approach. The sample in this study uses a total sampling technique of 45 samples. The data analysis presented was using univariate, bivariate and multivariate analysis. The results of this study were obtained as age variables with a pvalue of 0.012, education pvalue 0.028, house ventilation pvalue 0.016, water shelter condition pvalue 0.000, mosquito repellent with pvalue 0.014, clothes hanging place pvalue 0.016, waste disposal system pvalue 0.016. From dengue patients at the Muaradua Health Center, the condition of water reservoirs is the one that has the strongest effect compared to other facts (OlR 67,867). This can be interpreted if the respondent has an unhealthy water reservoir, he will have a risk of 67,867 times to suffer from dengue, and if he is old, he will have a similar risk.